Новые приключения Алисы: фантастические повести / Кир Булычев ; [художник К. Ли] - Булычев Кир (Юна, 1992)
Экземпляры: ф.1 (1999) / Инвентарный номер: 37515 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 90 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-445